Financing the 2016 Election - Magleby, David B. (Book collections on Project MUSE., 2019)
Financing the 2016 election explores the role of money in one of the most unconventional elections in modern American history: the presidential and congressional elections of 2016. David Magleby and his team of experts have examined Federal Elections Commission reports and interviewed dozens of key participants, including representatives of virtually all the major interest groups active in the 2016 election cycle. They place the election in the context of how U.S. elections have been financed during recent decades - a context that illustrates how dramatically different campaign finance is today from the past. Among the most important changes has been the growth of so-called super PACs, or political action committees, which have become incresaingly important both in the financing they provide candidates and in their ability to act independently, whether for or against candidates. Super PACs doubled their spending in 2016 from four years earlier. With its comprehensive yet readable approach, Financing the 2016 election helps readers understand how the financing of elections - including the increasing reliance by candidates on outside special interest groups - ultimately affects politics and public policy.